Durum-21: A New High-Yielding and Good Quality Durum Wheat Variety Suitable for Pasta Production - Javed Ahmad; Aziz ur Rehman; Iqra Ghafoor; Nadeem Ahmad; Muhammad Sarwar; Muhammad Abdullah; Muhammad Hammad Tanveer; Majid Nadeem; Sadia Ajmal; Ahsan Javed; et al. (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Durum-21 (D-21) is a high-yielding, disease resistant with better-quality traits variety, developed by Wheat Research Institute Faisalabad. This variety is mainly developed for industrial purposes for pasta production. Worldwide, durum wheat is utilized for pasta production; but in Pakistan, due to a lack of research work and non-availability of quality seeds of durum wheat, bread wheat is being utilized for pasta production. D-21 is developed with the breeding code of D-21 having parentage of FKN/3/2*FR//KAD/GB/4/BB/CHA/5/AS-2002 with pedigree as PB20733-1a-2a-2a-0a-0a-19a-0a. The candidate line D-21 was developed by crossing a germplasm accession with approved bread wheat variety AS-02. The genotype was further evaluated over multiple locations in Punjab Pakistan for yield and yield-related attributes in the station, provincial, and national uniform durum yield trials executed by Wheat Research Institute (WRI), Faisalabad during 2015-20. The promising line out yielded the two commercial check varieties D-97 and Fsd-2008 by 1.42 % in the provincial yield trial and 4.2 % in the national yield trial. D-21 had desirably medium to tall plant height (96-100 cm) without anthocyanin pigment. It has erected to semi-erect growth habit at the seedling stage. Its color is green with medium waxiness on stem and yellowish-white at maturity. Its 1000-grain weight ranged from 38.9 to 39 g while the test weight remained from 69 to 78.5 g. The protein contents were 13.1 to 14.95 %; which is higher than the two checks (D-97 and Fsd-2008). Due to its better grain yield and promising nutritional and quality parameters, it was approved in the year 2021 for cultivation all over the country.